Flying cheap [videorecording (DVD)] - Young, Rick ([Distributed by] PBS Home Video, 2010)
Frontline investigates the crash of Continental 3407 in Buffalo, NY, and discovers a dramatically changed airline industry, where regional carriers now account for half of the nation's daily departures. Insiders are worried that, thirty years after airline deregulation, the aviation system is being stretched beyond its capacity to deliver service that is both cheap and safe.